The Impact of Social Media on Society: Examining the Influence of Social Media Growth on Society (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Almost a quarter of the world’s population is now on Facebook. In the USA nearly 80 of all internet users are on this platform. Because social networks feed off interactions among people, they become more powerful as they grow.